A two-dimensional Ru@MXene catalyst for highly selective ambient electrocatalytic nitrogen reduction. Issue 20 (20th March 2020) - Liu, Anmin; Gao, Mengfan; Ren, Xuefeng; Meng, Fanning; Yang, Yanan; Yang, Qiyue; Guan, Weixin; Gao, Liguo; Liang, Xingyou; Ma, Tingli
Abstract : Compared with the traditional Haber–Bosch process, electrochemical ammonia synthesis has attracted much attention owing to its low energy consumption, low pollution potential, and sustainability. Abstract : Compared with the traditional Haber–Bosch process, electrochemical ammonia synthesis has attracted much attention owing to its low energy consumption, low pollution potential, and sustainability. However, owing to the influence of high overpotential and low selectivity, the nitrogen reduction reaction (NRR) process was of limited applicability in industry. Here, we report a high-performance Ru@Ti3 C2 MXene catalyst for an ambient electrocatalytic NRR. In a 0.1 M KOH electrolyte, the NH3 yield of the Ru@MXene catalyst reached 2.3 μmol h −1 cm −2, furthermore, at −0.4 V ( vs . RHE) the Faraday efficiency was 13.13%.